Problems of Translating Evasive Techniques in Journalistic Interviews - Qubais Saeed, Anfal (Opción, 2019)
Oral interpretation or consecutive translation is no longer an abstract study; it has become a language of communication between the different cultures. In- terpretation represents the container of all sciences and cultures, as it transfer the ideas and believe from a language to another. In other words, Interpreta- tion is not merely a linguistic process. It is more complex than substituting source language text/speech with target language text/speech and includes cultural and linguistic complicated processes which mange the translator to shape his translated text in a communicative way. As a transitional activity, it is necessary to highlight differences between translation and interpretation. Both of translation and interpretation are linguistic discipline, however, a good translator may not be a good interpreter, whereas, a good interpreter may not be good translator. Generally, the medium is not the only difference between translation and interpretation as the interpreter translates orally, whereas the translator interprets written texts. The process of interpretation needs addi- tional skills and qualifications. These qualifications include the knowledge of thesubjectsofinterpretation, familiaritywithbothSLandTLcultures,anda great ability of spontaneous paraphrasing. Both translation and consecutive interpretation are the arts of transferring knowledge of source language into a target language. A process that is confronted with linguistic and cultural ob- stacles. Consecutive interpreting (or oral translation) is a new academic top- ic that some researchers aim at separating it from the well-known academic written translation. The consecutive interpreting adds the oral dimension to the written translation. That is why the translation mistakes in consecutive interpreting involves new dimensions of pronunciation, besides the traditional translation mistakes such as semantic and lexical mistakes. The main aim of the study is highlight the main features and principles of translations of journal- istic interviews, such as silence “mis-translation,” changing the topic “ wrong-equivalent,” , over/under translation, transliteration, metaphor, cir- cumlocution, and ideology. Consequently, the study attempts at analyzing these problems through the given examples for introducing the recom- mended solutions for these problems. For achieving the study’s objectives, it is divided into an introduction, theoretical part with a discussion and a conclusion.